To find an expression equivalent to \( 9x^2 - 25 \) using the Distributive Property, we can recognize that this expression is a difference of squares. The difference of squares formula states that:
\[ a^2 - b^2 = (a - b)(a + b) \]
In the given expression \( 9x^2 - 25 \), we can identify:
- \( a^2 = 9x^2 \) so \( a = 3x \)
- \( b^2 = 25 \) so \( b = 5 \)
Now we can apply the difference of squares formula:
\[ 9x^2 - 25 = (3x)^2 - 5^2 = (3x - 5)(3x + 5) \]
Looking at the options provided, we see that the expression equivalent to \( 9x^2 - 25 \) is:
\((3x + 5)(3x - 5)\)
So the correct response is:
(3x+5)(3x−5)